2020
DOI: 10.1038/s41467-020-16288-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the inhibition mechanism of human sterol O-acyltransferase 1 by a competitive inhibitor

Abstract: Sterol O-acyltransferase 1 (SOAT1) is an endoplasmic reticulum (ER) resident, multitransmembrane enzyme that belongs to the membrane-bound O-acyltransferase (MBOAT) family. It catalyzes the esterification of cholesterol to generate cholesteryl esters for cholesterol storage. SOAT1 is a target to treat several human diseases. However, its structure and mechanism remain elusive since its discovery. Here, we report the structure of human SOAT1 (hSOAT1) determined by cryo-EM. hSOAT1 is a tetramer consisted of a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 68 publications
(72 reference statements)
1
55
0
2
Order By: Relevance
“…The absolutely conserved histidine residue that serves as one of the defining characteristics of MBOAT family members (H338 in GOAT) has been suggested to act as a general base in the acylation reactions catalyzed by these enzymes. (19,23,25,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) While this catalytic role has not been conclusively demonstrated in any MBOAT, the dependence of ligand 15 uptake on the presence on H338 in GOAT supports a direct interaction between the acylation site serine in ghrelin and this conserved histidine (Figure 2b). The enhanced binding affinity of ghrelin ligands with amine modifications at the serine acylation site likely arises from re-apportionment of the transition-state stabilization energy from the serine -histidine hydrogen bond/general base interaction during acyl transfer to ground-state binding enhancement from the amine/ammonium -histidine interaction in ligand 15.…”
Section: Discussionmentioning
confidence: 99%
“…The absolutely conserved histidine residue that serves as one of the defining characteristics of MBOAT family members (H338 in GOAT) has been suggested to act as a general base in the acylation reactions catalyzed by these enzymes. (19,23,25,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) While this catalytic role has not been conclusively demonstrated in any MBOAT, the dependence of ligand 15 uptake on the presence on H338 in GOAT supports a direct interaction between the acylation site serine in ghrelin and this conserved histidine (Figure 2b). The enhanced binding affinity of ghrelin ligands with amine modifications at the serine acylation site likely arises from re-apportionment of the transition-state stabilization energy from the serine -histidine hydrogen bond/general base interaction during acyl transfer to ground-state binding enhancement from the amine/ammonium -histidine interaction in ligand 15.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol ester, a major component of atherogenic lipoproteins, emerged to play a critical role in the development of atherosclerosis [ 48 ]. The enzyme sterol O-acyltransferases (Soat1 and Soat2), which catalyze the synthesis of CE from free cholesterol, are regarded as a potential target for atherosclerosis and hypercholesterolemia [ 49 , 50 ]. In the blood stasis rats, the significant accumulation of CE (20 : 5) might contribute to the overactivation of Soat enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of SOAT localized in the endoplasmic reticulum membrane had not been defined. Very recently, three research groups have just reported the structure of human-SOAT1 using cryo-electron microscopy [ 20 , 21 , 22 ]. Because SOAT1 and SOAT2 share extensive sequence homology, the structural properties of SOAT2 will be also elucidated in the near future.…”
Section: Discussionmentioning
confidence: 99%